2011
DOI: 10.1590/s1678-77572011005000016
|View full text |Cite
|
Sign up to set email alerts
|

Use of occlusal sealant in a community program and caries incidence in high- and low-risk children

Abstract: ObjectiveThe aims of this study were to investigate the effectiveness of sealant placement under the guidelines of the Oral Health Promotion Program for Children and Adolescents (Portugal), and to test the influence of clinical and socioeconomic variables on the DMFT increment in 277 children, born in 1997. Material and MethodsA dental hygienist performed the initial examinations and sealant placement (Helioseal, Vivadent) on the permanent first molars in 2005. These activities were registered in dental record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 27 publications
1
19
0
6
Order By: Relevance
“…The impact of this risk factor on the effect of sealants appears to be very relevant, because unlike potential clinical and biological risk factors retained due to their high credibility, carious lesions ICDAS 3‐6 is the sole unanimously recognized factor (risk predictor) by which to assess the ICR, in the absence of consensus for ICR assessment. Thus, the present study confirmed the substantial interest of SBDS programs focusing on high caries risk children (individual level) rather than risk schools (community level), stipulating a particular risk factor, carious lesions ICDAS 3‐6. The rationale for applying the SBDS programs focusing on high caries risk children has already been recommended in earlier cost‐effectiveness studies, in different countries corresponding to different social models.…”
Section: Discussionsupporting
confidence: 65%
“…The impact of this risk factor on the effect of sealants appears to be very relevant, because unlike potential clinical and biological risk factors retained due to their high credibility, carious lesions ICDAS 3‐6 is the sole unanimously recognized factor (risk predictor) by which to assess the ICR, in the absence of consensus for ICR assessment. Thus, the present study confirmed the substantial interest of SBDS programs focusing on high caries risk children (individual level) rather than risk schools (community level), stipulating a particular risk factor, carious lesions ICDAS 3‐6. The rationale for applying the SBDS programs focusing on high caries risk children has already been recommended in earlier cost‐effectiveness studies, in different countries corresponding to different social models.…”
Section: Discussionsupporting
confidence: 65%
“…[10,13–15] However, a study developed by Martin et al . (2013) concludes that dentists may be underusing fissure sealants, even when knowing that a fissure sealant is effective and has positive effects on the prevention of oral diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Auch in der Literatur wird berichtet, dass Kinder, die mindestens eine FV aufweisen, ein geringeres Risiko eines Kariesbefalls der bleibenden Zähne haben [33,34]. Neben der FV beeinflussen weitere individualprophylaktische Maßnahmen, wie Fluoridierung, Mundhygieneinstruktionen und Aufklärung zur Kariesätiologie die Kariesentstehung und -progression [35,36].…”
Section: Diskussionunclassified